1987
DOI: 10.1111/j.1365-2125.1987.tb03147.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and platelet intracellular free calcium concentrations.

Abstract: The effect of 0.8 g kg‐1 absolute ethanol orally on platelet intracellular free calcium was assessed in a random order study in 24 normotensive subjects with an isocaloric control. Platelet calcium was measured 90 min and 12 h after treatment by the Quin 2 method. The study had 90% power of detecting a 16.5% change. After 90 min, breath ethanol was 37 +/‐ 9 micrograms 100 ml‐1, blood pressure was unchanged and heart rate rose slightly. Platelet calcium was unchanged by ethanol after 90 min or 12 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…In addition, as far as we know, no significant association between the volume of alcohol consumed and cytosolic-free calcium concentrations in the platelets has been confirmed in the studies on human drinkers. 26,27 A close association between serum GGT and BP in alcohol consumers was observed in the present study, and has been repeatedly shown in our previous studies [28][29][30] and in those of other researchers. 31,32 It suggested an association between hepatic manifestations induced by alcohol, mainly steatosis in the liver, and BP elevation.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, as far as we know, no significant association between the volume of alcohol consumed and cytosolic-free calcium concentrations in the platelets has been confirmed in the studies on human drinkers. 26,27 A close association between serum GGT and BP in alcohol consumers was observed in the present study, and has been repeatedly shown in our previous studies [28][29][30] and in those of other researchers. 31,32 It suggested an association between hepatic manifestations induced by alcohol, mainly steatosis in the liver, and BP elevation.…”
Section: Discussionsupporting
confidence: 90%